Sputtering thin films: Materials, applications, challenges and future directions - Garg R.; Gonuguntla S.; Sk S.; Iqbal M.S.; Dada A.O.; Pal U.; Ahmadipour M. (Elsevier B.V., 2025)
Sputtering is an effective technique for producing ultrathin films with diverse applications. The review begins by providing an in-depth overview of the background, introducing the early development of sputtering and its principles. Consequently, progress in advancements made in recent decades highlights the renaissance of sputtering as a powerful technology for creating thin films with varied compositions, structures, and properties. For the first time, we have discussed a thorough overview of several sputtered thin film materials based on metal and metal oxide, metal nitride, alloys, carbon, and ceramic-based thin film along with their properties and their applicability in various fields. We further delve into the applications of sputter-coated thin films, specifically emphasizing their relevance in environmental sustainability, energy and electronics, and biomedical fields. We critically examine the recent advancements in developing sputter-coated catalysts for eliminating water pollutants andhydrogen generation. Additionally, the review sheds light on advantages, shortcomings, and future directions for developing sputter-coated thin films utilized in biodegradable metals and alloys with enhanced corrosion resistance and biocompatibility. This review is a comprehensive integration of recent literature, covering diverse sputtering thin film applications. We delve deeply into various material types and emphasize critical analysis of recent advancements, particularly in environmental, energy, and biomedical fields. By offering insights into both advancements and limitations, the review provides a nuanced understanding essential for practical utilization. ? 2023